Adsorption equilibria between dye and surfactant in single and binary systems onto geological materials - CANTÜRK TALMAN, REMZİYE YEŞİM (ELSEVIER SCIENCE BV, 2009)
Adsorption characteristics of cationic dyes and surfactants onto clay and sandstone from a single component system were studied using toluidine blue (TB) and cetyl trimethylammonium bromide (CTAB). Equilibrium data of TB and CTAB in the single solute systems fit well to the Langmuir and the Freundlich adsorption isotherms. Competitive adsorption was observed between dye and surfactant cations. The effect of sodium chloride on dye and surfactant adsorption was studied in TB-NaCl and CTAB-NaCl binary systems. Equilibrium adsorption for binary systems was analyzed by using the extended Langmuir and the extended Freundlich models. Adsorption results for the TB-CTAB system onto both adsorbents were also well described by the Sheindorf-Rebuhn-Sheintuch (SRS) model for multi-component systems. Free energy changes for adsorption systems were calculated using thermodynamic equilibrium constants evaluated from selectivity coefficients of the binary systems. The site distribution functions estimated using Freundlich model parameters gave valuable information about the ratio of the adsorption sites on adsorbent surface having different affinity for competing cations. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Toluidine blue; CTAB; Competitive adsorption; Clay; Sandstone; CATION-EXCHANGE CAPACITY; BAGASSE FLY-ASH; METHYLENE-BLUE; AQUEOUS-SOLUTIONS; FULLERS EARTH; BASIC DYE; CLAY; BENTONITE; REMOVAL; MONTMORILLONITE